Investigation of the Thermal, Kinetic, and Dielectric Properties of a Novel Methacrylate Polymer Derived from Naphthol-Containing Cinnamic Acid Derivative - Çalışkan, Eray; Koran, Kenan; Biryan, Fatih (My University, 2023)
The study investigates the thermal, kinetic, and dielectric properties of a novel methacrylate polymer synthesized from a naphthol-containing cinnamic acid derivative. Notably, the glass transition temperature (Tg) of the polymer, a crucial parameter for amorphous polymers, was found to be significantly higher than traditional methacrylate polymers, owing to the presence of the naphthol group within the polymer structure. The research also delves into the thermal stability and activation energy of the polymer using thermal analysis techniques. Additionally, the dielectric properties of the homopolymer were explored with a focus on the temperature-dependent changes in the dielectric constant and its behavior with varying frequencies.
Keywords: Polymer; Thermal stability; Dielectric; Cinnamic acid